2017
DOI: 10.1093/mnras/stx1503
|View full text |Cite
|
Sign up to set email alerts
|

Star-forming galaxies in intermediate-redshift clusters: stellar versus dynamical masses of luminous compact blue galaxies

Abstract: We investigate the stellar masses of the class of star-forming objects known as Luminous Compact Blue Galaxies (LCBGs) by studying a sample of galaxies in the distant cluster MS 0451.6-0305 at z ≈ 0.54 with ground-based multicolor imaging and spectroscopy. For a sample of 16 spectroscopically-confirmed cluster LCBGs (colour B − V < 0.5, surface brightness µ B < 21 mag arcsec −2 , and magnitude M B < −18.5), we measure stellar masses by fitting spectral energy distribution (SED) models to multiband photometry, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…We note however that our CDS sample is more narrowly defined in mass than both blue E/S0s and the higher-mass extension of BCDs, luminous blue compact galaxies (BCGs), which are rare at z ∼ 0. Blue E/S0s and luminous BCGs can have masses well above the gas-richness threshold scale at M * ∼ 10 9.5 M (e.g., Schawinski et al 2009;Kannappan et al 2009;Östlin et al 2015;Randriamampandry et al 2017). Detailed studies (Östlin et al 2004;Marquart et al 2007;Cumming et al 2008;Östlin et al 2015) of BCGs in the local universe have shown that these objects regularly exhibit irregular kinematics and secondary dynamical components akin to those we see in §4.2.3, consistent with merger formation, although some BCGs are also observed to have companions (Östlin et al 2004;Cumming et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…We note however that our CDS sample is more narrowly defined in mass than both blue E/S0s and the higher-mass extension of BCDs, luminous blue compact galaxies (BCGs), which are rare at z ∼ 0. Blue E/S0s and luminous BCGs can have masses well above the gas-richness threshold scale at M * ∼ 10 9.5 M (e.g., Schawinski et al 2009;Kannappan et al 2009;Östlin et al 2015;Randriamampandry et al 2017). Detailed studies (Östlin et al 2004;Marquart et al 2007;Cumming et al 2008;Östlin et al 2015) of BCGs in the local universe have shown that these objects regularly exhibit irregular kinematics and secondary dynamical components akin to those we see in §4.2.3, consistent with merger formation, although some BCGs are also observed to have companions (Östlin et al 2004;Cumming et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Cluster and field populations of LCBGs show no significant difference in size, mass, luminosity, star formation rate, or metallicity (Crawford et al 2016). Randriamampandry et al (2017) found cluster LCBGs have a lower dynamical to stellar mass ratio than field LCBGs at intermediate redshift, indicating the mass of field LCBGs is more highly dominated by dark matter. Guzmán et al (1997) and Phillips et al (1997) found that LCBGs are similar to local HII star-forming galaxies, they constitute ∼45% of the star formation rate density and ∼20% of the galaxy population at z=0.6, and show no evolution in specific star formation rate.…”
Section: Introductionmentioning
confidence: 81%
“…Previous studies of LCBGs have concentrated on small snapshots in time, often being limited to low or intermediate redshift. Intermediate redshift (z∼0.5) studies have looked at LCBG morphology (Noeske et al 2006) and spectral properties (Tollerud et al 2010), environment (Crawford et al 2005(Crawford et al , 2014(Crawford et al , 2016Randriamampandry et al 2017), and number density (Phillips et al 1997;Guzmán et al 1997). LCBGs make up about 50% of the socalled Butcher-Oemler population of blue galaxies in clusters between redshift, 0.55<z<1 (Crawford et al 2005), and are likely on their initial descent into a cluster (Crawford et al 2014).…”
Section: Introductionmentioning
confidence: 99%